The use of betel (Piper betle) leaves for maintaining the health of women and children at various ethnic groups in Indonesia - Lucie Widowati; Lestari HAndayani; Rohmat Mujahid (Smujo International, 2020)
Abstract. Widowati L, Handayani L, Mujahid R. 2020. The use of betel (Piper betle) leaves for maintaining the health of women and children at various ethnic groups in Indonesia. Nusantara Bioscience 12: 120-126. Betel is considered as one of the popular medicinal plants. Traditional uses of betel are mainly for maternal and child health, and frequently applied by the local communities. The study was carried out to determine the traditional use of betel. The method used a descriptive approach by analyzing the data collected from the RISTOJA Project in the year of 2012, 2015, and 2017. Data collection was conducted in 34 provinces of Indonesia through the survey of local knowledge of ethnomedicine and community-based medicinal plants. We collected the data using semi-structured interviews with traditional healers. The study revealed some medicinal related purposes, such as (i) Beauty care/cosmetic; (ii) Female genital organ; (iii) Fertility disorders; (iv) Pre and postnatal; (v) Stimulating breast milk, and (vi) Baby and children care. The RISTOJA project proved that the use of betel in health care for women and children is a lot so that it should be more developed. Previous studies also proved that betel is efficacious and safe for women and children. On the contrary, unhygienic way of services in traditional rituals and beliefs need to be supervised so that there is no harmful effect on the consumer. We propose establishing guidance to the traditional healers so that they can understand the safety and efficacy of traditional medicine and hygienic traditional health services.